Clinical pharmacology of cephalexin administered by intravenous injection - Davies, J. A. (1972)
Cephalexin IG was given by intravenous injection to eight normal volunteers, five patients with chronic renal failure, and three patients during a period of haemodialysis. In normal subjects there was a rapid fall in serum concentration and 80% of the administered dose was excreted in the urine within two hours. The mean serum half life was 1·1 hours (range 0·6-1·8 hours). Prior treatment with probenecid in two subjects led to a twofold increase in serum concentration two hours after injection. In the patients with chronic renal failure antimicrobial activity persisted for 24 hours and the half life ranged from 6·1 to 18·1 hours. Haemodialysis led to partial removal of cephalexin from the blood, but antimicrobial activity remained eight hours after injection at the end of the dialysis period. The serum half life in these patients was 5·1, 5·6, and 5·7 hours.